Responsabilidad Patrimonial del Estado por la privacidad injusta de la libertad (2018)
It is evident that every day there is an increase in the number of demands for the means of control of direct reparation, impetrated by the personnel that has been acquitted in a criminal proceeding and they consider that the State has the duty to compensate them for the time they lasted deprived of freedom, even in cases of preventive detention, better known as an assurance measure to guarantee the appearance of the subject to the criminal process. The National Agency for Legal Defense of the State, has stated that within its powers is to formulate public policies in matters of prevention of unlawful public conduct, unlawful damage and the extension of its effects (Decree 4085 of 2011, Article 2), and in recent years has expressed concern about the numerous litigation facing the State in the matter of unjust deprivation of liberty, manifested the need to acquire theoretical bases and empirical evidence to indicate what is the thinking of the high courts in this matter and what have been the assumptions that have allowed the current jurisprudence to draw the dominant opinion on this issue. In addition, it is evident that every day the causes of the patrimonial responsibility of the State have been extended, which can have great consequences in the economic sphere of the State and impede the development of the country. We will provide an analysis from the substantial point of view of the responsibility of the State for judicial activity in Colombia, taking as its main axis the State's responsibility for unjust deprivation of liberty, as that consequence of the damages produced with the provisional prison, determining the foundation of the notion of unlawful damage and relying on the different interpretations of the high courts on the subject